Basket Trials for Intractable Cancer - Qin, Bao-Dong; Jiao, Xiao-Dong; Liu, Ke; Wu, Ying; He, Xi; Liu, Jun; Qin, Wen-Xing; Wang, Zhan; Zang, Yuan-Sheng (Frontiers in Oncology, 2019)
Currently, genomic characterization has become standard of care for tumor types such as non-small cell lung cancer, breast cancer, melanoma, and colorectal cancer. A deep understanding of genomic alterations in different tumor types would help identify potentially actionable genomic changes which occur across a wide variety of tumor types. A basket trial is a new type of clinical trial for which eligibility is based on the presence of a specific genomic alteration, irrespective of histology. Basket trials are phase II screening trials for the off-label use of a targeted drug in patients with the same genomic alterations for which it was approved. Intractable cancer refers to a type or condition of cancer which is unresponsive or resistant to treatment; intractable cancers may be classified into five subtypes as follows: hard-to-treat condition of common advanced cancer after multiple-line therapy, rare cancer in which no standard of care has been recommended, advanced cancer in which standard of care does not work well, cancer accompanied with organ dysfunction, and cancers in older or younger cancer patients. Previous studies have demonstrated that in basket trials, genomic-guided therapy yields clinical benefits in intractable cancer, thereby providing novel insights into the optimal clinical management of such cancers. In this review, we describe a novel way to classify intractable cancer, and summarize the current knowledge on such cancers. We additionally provide information on the role of basket trials in intractable cancer.